Epidemiological studies on patients with a persistent vegetative state. Issue 9 (September 1977) - Higashi, K.; Sakata, Y.; Hatano, M.; Abiko, S.; Ihara, K.; Katayama, S.; Wakuta, Y.; Okamura, T.; Ueda, H.; Zenke, M.; Aoki, H.
Abstract : Persistent vegetative state after severe brain damage was studied epidemiologically in 110 cases from 1973 to 1976. The causes of brain damage were varied. More than one-third of the cases were due to trauma, and about one-fifth were the result of vascular accidents. Three year observation revealed that 65% of the patients died during this period. Mean survival time for dead patients was 38 months. Reactivity, clinical signs, EEG findings, methods of management, and results of various trials of treatment were investigated in connection with the patient's prognosis.